The prognostic value of the triglyceride-glucose index in predicting recurrence of acute pancreatitis: a retrospective cohort study - Lihui Lin; Yansong Lin; Xin Ling; Zewen Zhang; Xianwen Guo; Zhen Ding (Nutrition & Metabolism)
Abstract Background Investigating the risk of acute pancreatitis (AP) recurrence is crucial because it affects public health and medical resources. The triglyceride–glucose index (TyG-i) is recognized as a reliable marker of insulin resistance (IR), which occurs after an AP attack. However, the predictive value of the TyG-i during the first AP for subsequent recurrence remains unclear. Methods Patients with their first AP episode between January 2014 and December 2023 were followed up retrospectively. Data on demographic characteristics, imaging findings, and laboratory examinations of their first episode and recurrences were collected. The TyG-i was calculated as follows: ln [fasting triglyceride (mg/dL) × fasting glucose (mg/dL)/2]. Factors associated with AP were evaluated using Cox regression analyses. Results A total of 853 patients were enrolled in our study, 180 (21.1%) of whom experienced a recurrence after the first AP episode. The recurrence rate was higher in the high TyG-i index group (n = 111, 26.0%) than in the low TyG-i index group (n = 69, 16.2%; P < 0.001). Cox regression analyses revealed TyG-i as an independent predictor of AP recurrence in all etiologies (hazard ratio [HR] = 1.535, P = 0.007), as well as for the recurrence of acute biliary pancreatitis (HR = 1.829, P = 0.035). Conclusion TyG-i status at the first AP episode could independently predict recurrence.